2004
DOI: 10.1074/jbc.m311579200
|View full text |Cite
|
Sign up to set email alerts
|

The Aqueous Accessibility in the External Half of Transmembrane Domain I of the GABA Transporter GAT-1 Is Modulated by Its Ligands

Abstract: The sodium-and chloride-dependent ␥-aminobutyric acid (GABA) transporter GAT-1 is the first identified member of a family of transporters, which maintain low synaptic neurotransmitter levels and thereby enable efficient synaptic transmission. To obtain evidence for the idea that the highly conserved transmembrane domain I (TMD I) participates in the permeation pathway, we have determined the impact of impermeant methanethiosulfonate (MTS) reagents on cysteine residues engineered into this domain. As a backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…In GAT-1, GABA reduced the reactivity of cysteines located in the extracellular access pathway (25,31). However, in several cases, the non-transportable analogue SKF100330A did not potentiate but protected (31), presumably by a physical blockade of the sulfhydryl reagent by the bulky blocker. Altogether, the present work and the previous studies suggest a concerted conformational change involving opposite accessibility changes in external and internal pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In GAT-1, GABA reduced the reactivity of cysteines located in the extracellular access pathway (25,31). However, in several cases, the non-transportable analogue SKF100330A did not potentiate but protected (31), presumably by a physical blockade of the sulfhydryl reagent by the bulky blocker. Altogether, the present work and the previous studies suggest a concerted conformational change involving opposite accessibility changes in external and internal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several residues in the intracellular part of TM 5 of SERT reacted faster in the presence of substrate and slower in the presence of a non-transportable analogue and were proposed to line the intracellular pathway leading to the binding pocket (16). In GAT-1, GABA reduced the reactivity of cysteines located in the extracellular access pathway (25,31). However, in several cases, the non-transportable analogue SKF100330A did not potentiate but protected (31), presumably by a physical blockade of the sulfhydryl reagent by the bulky blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Despite only 20 -25% sequence identity between LeuT and its eukaryotic counterparts, there is high conservation in the TMs 1, 3, 6, and 8 that surround the leucine binding site (11). Biochemical studies on mammalian transporters had identified, previously, that residues in TM1 (22,23) and TM3 (12,13,24,25) were important for substrate binding and transporter function.…”
Section: Discussionmentioning
confidence: 99%
“…Two TMD 3 residues of SERT, corresponding to leucine 136 and isoleucine 143 of GAT-1, are located one turn of a putative ␣-helix below or above the critical tyrosine 176, respectively (17). The highly conserved TMD 1, which appears to line the permeation pathway and appears to form a more extended structure than expected from a membrane-embedded ␣-helix (18,19), contains several amino acid residues critical for function. They have been implicated in playing an important role in the interaction with the neurotransmitter (20,21), in the determination of the apparent affinity for sodium (21,22), and in the sodium-dependent conversion of the leak mode of the transporter into the coupled mode (21).…”
mentioning
confidence: 99%